(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the technology for developing interpersonal relationship culture among primary school students in the mother tongue education process. It specifically highlights that group work during mother tongue lessons is one of the most effective means of fostering interpersonal relationship culture among students. The article also analyzes the appropriateness of organizing collective creative activities with students to model real-life situations in the classroom.